AD, Volume 2, n° 3, 1977 - Full Issue (Africa Development, 1977)
Contents — Sommaire Abdalla S. Bujra Editorial ................................ 5 ARTICLES Abdelkader Sid Ahmed Sous-développement, Industrialisation et Dépendance ......................... 11 Summary ................................ 26 Delphin Rwegasira Inflation and Economie Development : Some Lessons from the Tanzanian Experience ................ 29 Résumé .......................... 49 Hussein M. Mirghani The Effect of the International Monetary Crisis on Capital Inflows to Sudan. A preliminary Note ........................ 51 Résumé .......................... 57 Wilfred A. Ndongko The Financing of Economic Development in Cameroon ........................ 59 Résumé ............................ 75 Luabeya Kabeya Foreign Financial Assistance and Economic Growth in Zaire ...................... 77 Résumé BOOK REVIEWS - REVUE DES LIVRES B. Founou - Tchigoua Formation du Sous-développement en Algérie, par Abdellatif Benachenhou .......................... 97 Liberty Mhlanga Outer Limits and Human Needs, ed. b byH.Matthews ........................... 103 FOCUS ON RESEARCH AND TRAINING INSTITUTES Centre for Development Studies, University of Cape Coast, Ghana ...................... 109 Institut des Relations Internationales du Cameroun, Université de Yaoundé ............................... 113